The Impact of COVID-19 Lockdown on Injuries in Saudi Arabia: Results From a Level-I Trauma Center - Hakeem, Faisal F.; Alshahrani, Saeed Mastour; Ghobain, Mohammed Al; Albabtain, Ibrahim; Aldibasi, Omar; Alghnam, Suliman (Frontiers in Public Health, 2021)
Background: The COVID-19 pandemic has placed an enormous strain on global health. Due to precautionary measures, the epidemiology of health conditions may have been affected. Saudi Arabia imposed a lockdown order on March 25, 2020. This study investigated the impact of the pandemic lockdown on injuries in a level-I trauma center in King Abdulaziz Medical City, Riyadh, Saudi Arabia. Methods: This retrospective study identified all injured patients seeking emergency care during the lockdown period (March 25–June 21, 2020) and a similar period in two previous year (March 25–June 21) 2018 and 2019. The collected data included patients' demographics, injury types, mechanisms, and health outcomes. Results: Two hundred sixty nine injured patients sought emergency care during the lockdown, while 626 and 696 patients were treated in the same period of 2018 and 2019, respectively. There was a significant reduction in motor vehicle crashes (OR: 0.47; 95% CI: 0.31–0.73) and burns (OR: 0.24; 95% CI: 0.08–0.66), coupled with a significant increase in assault injuries (OR: 2.20; 95% CI: 1.30–3.74) in the lockdown period compared to 2019. Apart from the intensive care unit (ICU) admission and hospital length of stay, there were no differences between the two periods in the health outcomes. ICU admission was significantly reduced by 57% during the lockdown period (OR: 0.43; 95% CI: 0.22–0.83). Mechanisms of injuries were not significant predictors of deaths or ICU admission or both in the lockdown period. Conclusion: The COVID-19 lockdown had a clear impact on the volume and mechanisms of injuries. The findings highlight that injury risk factors are modifiable and emphasize the importance of public health measures for preventing injuries and the significance of maintaining trauma services capacity during pandemics.